Analisis Pengembangan Media SIGIMU Berbasis Modalitas Belajar pada Pembelajaran Tematik - Elsaputri, Halida Rianti; Bahrodin, Ariga (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to analyze the development of SIGIMU (Dental and Oral Education) media based on learning modalities in class I thematic learning according to students. Data obtained from the results of student questionnaires were then analyzed descriptively and qualitatively. The results of the analysis of SIGIMU media development in terms of media, namely the cover design according to the content, type and size of letters suitable for class I students, attractive pictures and colors according to the learning modalities of students. Regarding preparing the material, it is relevant to the competencies that students, font type, size, and attractive colors must master. From a child's psychological perspective, SIGIMU media can attract interest in learning, facilitate students to experience learning according to their tendency to absorb information and accommodate students' learning styles. In terms of use, the media can be used easily, both independently and together. The material is complete with illustrated crossword bonuses by activities to maintain dental and oral health. It can also encourage curiosity and support students to act, as the media exemplifies. So the development of SIGIMU media is very interesting, suitable for thematic learning, and can be used according to student learning modalities, both visual, auditory, and kinesthetic.Keywords: Analysis, Development, Learning Media, Dental and Oral Education, Learning Modalities